Cheche : reminiscences of a radical magazine - Hirji, Karim F. (Mkuki Na Nyota Publishers, 2010)
Cheche, a radical, socialist student magazine at the University of Dares Salaam, first came out in 1969. Featuring incisive analyses of key societal issues by prominent progressives, it gained national and international recognition in a short while. Because it was independent of authority, and spoke without fear or favor, it was banned after just a year of existence. The former editors and associates of Cheche revive that salutory episode of student activism in this book with fast-flowing, humor spiced stories, and astute socio-economic analyses. Issues covered include social and technical aspects of low-budget magazine production, travails of student life and activism, contents and philosophy of higher education, socialism in Tanzania, African liberation, gender politics and global affairs. They also reflect on the relevance of past student activism to the modern era. If your interests cover higher education in Africa, political and development studies, journalism, African affairs, socialism and capitalism, or if you just seek elucidation of student activism in a nation then at the center of the African struggle for liberation, this book presents the topic in a lively but unorthodox and ethically engaging manner.